2021
DOI: 10.1186/s12911-021-01599-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical decision support system RHINA in the diagnosis and treatment of acute or chronic rhinosinusitis

Abstract: Background Rhinosinusitis is an inflammation of the sinonasal cavity which affects roughly one in seven people per year. Acute rhinosinusitis (ARS) is mostly, apart from allergic etiology, caused by a viral infection and, in some cases (30–50%), by a bacterial superinfection. Antibiotics, indicated only in rare cases according to EPOS guidelines, are nevertheless prescribed in more than 80% of ARS cases, which increases the resistant bacterial strains in the population. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This study identified the gap between antibiotic prescribing guidelines and the clinical practice for treatment of acute sinusitis treatment in outpatient settings. Based on these findings, the antibiotic prescription rate among acute sinusitis cases is higher (90.8%) than reported in previous studies (Ginzburg et al, 2018;Hart et al, 2021;Hughes et al, 2020). Providers did not consistently adhere to the antibiotic prescribing guidelines for acute sinusitis.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…This study identified the gap between antibiotic prescribing guidelines and the clinical practice for treatment of acute sinusitis treatment in outpatient settings. Based on these findings, the antibiotic prescription rate among acute sinusitis cases is higher (90.8%) than reported in previous studies (Ginzburg et al, 2018;Hart et al, 2021;Hughes et al, 2020). Providers did not consistently adhere to the antibiotic prescribing guidelines for acute sinusitis.…”
Section: Discussionmentioning
confidence: 56%
“…This RCR found that 90.8% of acute sinusitis cases received an antibiotic prescription. Previous studies found that more than 80% of adult acute sinusitis cases received antibiotics (Hart et al, 2021; Hughes et al, 2020; & Ginzburg et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation